New genera and species of the tribe Parahiraciini (Hemiptera: Fulgoroidea: Issidae) - Gnezdilov, Vladimir M. (Acta entomologica slovenica (Ljubljana), 2005)
Pinocchias natus and Narinosus nativus - two new genera and two new species of the tribe Parahiraciini Cheng & Yang are described from India and China.
Keywords: Hemiptera; India; Indija; insekti; Kitajska